Effect of biostimulant raw materials on soybean (Glycine max) crop, when applied alone or in combination with herbicides - Franzoni, Giulia; Bulgari, Roberta; Florio, Francesco Elia; Gozio, Enrico; Villa, Daniele; Cocetta, Giacomo; Ferrante, Antonio (Frontiers in Agronomy, 2023)
Biostimulants exert positive functions in plants, improving yield and quality, and alleviating the negative effects of abiotic stresses. Among them, the application of herbicides may cause damage to nontarget plants. At present, limited information is available regarding the interaction between biostimulants and herbicides. The purpose of the present study was to assess the effect of an herbicide’s mixture (Harmony® 50 SX® + Tuareg® + Zetrola®), used in combination with several biostimulant raw materials (BRM), on the agronomic and physiologic characteristics of soybean. The experiments were conducted in two seasons, 2020 and 2021, applying the herbicides mixture alone or associated with 10 BRM. Differences emerged between the two years, considering nitrate, total sugars concentration, flavonol, and chlorophyll a fluorescence-related parameters. Chlorophyll content significantly declined (-45 % in 2020) in plants treated with the herbicides mixture alone but, in combination with potassium silicate, the chlorophyll values were restored to control levels. The same positive effect observed in response to the combination of potassium silicate and the herbicide mixture has been confirmed in the second year of experiment. At the same time, chlorophyll content and Nitrogen Index were positively increased (up to 8 % and 30 %, respectively) depending on the application of some BRM and the year. A significant effect of biostimulants on yield was confirmed by the application of Ascophyllum nodosum (+16%) and humic acids (+ 7%), in 2020. However, the combined use with the herbicides nullifies the increase. The results obtained from these experiments support the use of biostimulants in improving specific quality traits (chlorophyll content, leaves nitrogen status, and secondary metabolites accumulation). At the same time, the potential use of biostimulants in combination with herbicides needs to be further explored since of external factors (environment, year…) still have a strong effect on their efficacy.